Reproducibility of Direct Quantitative Measures of Cortical Bone Micro-architecture of the Distal Radius and Tibia by HR-pQCT - Burghardt, Andrew J. (2010)
Quantitative cortical micro-architectural endpoints are important for understanding structure-function relations in the context of fracture risk and therapeutic efficacy. This technique study details new image-processing methods to automatically segment and directly quantify cortical density, geometry, and micro-architecture from HR-pQCT images of the distal radius and tibia. An automated segmentation technique was developed to identify the periosteal and endosteal margins of the distal radius and tibia, and detect intra-cortical pore space morphologically consistent with Haversian canals. The reproducibility of direct quantitative cortical bone indices based on this method was assessed in a pooled dataset of 56 subjects with two repeat acquisitions for each site. The in vivo precision error was characterized using root mean square coefficient of variation (RMSCV%) from which, the least significant change (LSC) was calculated. Bland-Altman plots were used to characterize bias in the precision estimates. The reproducibility of cortical density and cross-sectional area measures was high (RMSCV <1% and <1.5%, respectively) with good agreement between young and elder medians. The LSC for cortical porosity (Ct.Po) was somewhat smaller in the radius (0.58%) compared with the distal tibia (0.84%) and significantly different between young and elder medians in the distal tibia (LSC: 0.75% vs. 0.92%; p<0.001). The LSC for pore diameter and distribution (Po.Dm and Po.Dm.SD) ranged between 15 and 23μm. Bland-Altman analysis revealed moderate bias for integral measures of area and volume, but not density nor microarchitecture. This study indicates HR-pQCT measures of cortical bone density and architecture can be measured in vivo with high reproducibility and limited bias across a biologically relevant range of values. The results of this study provide informative data for the design of future clinical studies of bone quality.